The Relative Importance of Vascular Risk Factors on Early Cognitive Aging Varies Only Slightly Between Men and Women - Bonberg, Nadine; Wulms, Niklas; Berger, Klaus; Minnerup, Heike (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the sex-specific course and impact of vascular risk factors on cognitive aging in a rather young and healthy community-dwelling cohort. Methods: We used data of a population-based cohort study, collected three times during six years, comprising 1911 examinations from 798 participants aged 35-66 years at baseline. Cognitive performance on the Color-Word-Interference-Test, the Trail Making Tests A&B, the Word Fluency Test, a 12-item word list, and the Purdue Pegboard Test and a principal component global score were used as outcomes in linear mixed models. We evaluated (1) sex-differences in cognitive trajectories, (2) the mediating role of hypertension, diabetes, smoking and obesity (BMI>30) on sex-differences, and (3) in sex-stratified analyses, potential sex-specific effects of these risk factors on cognition. Results: For all cognitive tests, we observed cognitive decline with age. Rates of decline slightly differed between sexes, showing a later but steeper decline for women in tests of memory (word list) and word fluency, but a steeper decline for men in tests of psychomotor speed and mental set shifting (TMT A&B) in older age. Women generally scored better on cognitive tests, but the slightly higher prevalence of classical vascular risks factors in men in our cohort could not explain these sex-differences. Sex-stratified analyses revealed a generally small, concordantly negative, but quantitatively slightly different impact of diabetes, smoking, and obesity on cognitive functions but mixed effects for arterial hypertension, depending on the blood pressure values, the treatment status, and the duration of arterial hypertension. Conclusion: Cognitive sex-differences in this rather young and healthy cohort could not be explained by a differing prevalence of vascular risks factors across sexes. The association of cardiovascular risk factors on cognition, however, slightly differed between men and women, whereby effects were generally small. Whereas longtime diabetes, obesity, and smoking had a sex-specific, but concordantly negative impact on psychomotor speed, executive and motor functions, we found some opposing effects for arterial hypertension. Our results can help to identify sex-specific susceptibilities to modifiable risk factors, to attract attention to potential information bias, and to stimulate further research into alternative causes of mechanism of sex-differences in cognitive aging.